Income and Differential Fertility: Evidence from Oil Price Shocks - Abebe Hailemariam (Global Labor Organization (GLO), 2022)
This paper examines the effect of national income on the total fertility rate (children born per woman). We estimate the effects on fertility of shocks to national per capita income using plausibly exogenous variations in oil price shock as an instrument for income and using instrumental variable generalized quantile regressions (IV-GQR). Using data for a panel of 122 countries spanning the period 1965-2020, our results show that national per capita income has has generally a negative and significant effect on the total fertility rate. Looking at the entire spectrum of the fertility distribution, the IVGQR estimates exhibit considerable heterogeneity in the impact of income on fertility. The income elasticity of fertility is relatively low at the upper tail of the distribution (for countries with high fertility) compared to the value at the median.
Keywords: J11; J13; O11; 330; national income; differential fertility; mortality; oil price shock; instrumental variable generalized quantile regressions